Fundamentalisme Agama Masyarakat Pluralis dan Humanis - Imam Syafi'ie (Unisia, 2002)
In the beginning of century 21 that signed by the great changes, the clash of civilization and social conflict happening all over the world. But, the religion still plays important role in the process of globalization. In this sense, the fact, the followers of religion face the community consciousness that the structural adjustment and the cultural understanding denote irrefutable. The author tries to investigate the role of religion in the global era, which characterized by the rapid change and it is difficult to predict. This article contains the definition and the characteristics of the global era, the fundamentalism of religion, and the role of religion in the recent era. Besides, it describes the plurality of religion, conflict and integration; it also looks for the formulation how to rebuild Muslim civilization.